Audit assessment of the facilities maintenance management in a public hospital in Malaysia - Ali, Maisarah; Wan Mohamad, Wan Mohamad Nasbi (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to assess the existing facilities maintenance management practices and processes in public hospitals, in accordance with the concession agreement (CA), in order to identify the current performance status.